The Evidential Power of a Private Deed Legalized by a Notary in Court - Ikstian, Shandy Fanyahya (Jurnal Konstatering, 2024)
The evidentiary power of a private deed as evidence in a court proceeding that is connected to the notary's authority in legalization. This study aims to determine the strength of a private deed as evidence in a court proceeding, to determine whether or not the legalization function of a deed made privately can provide additional evidentiary power in a court hearing. Based on the results of the study, it can be seen that: 1) The practice of legalization by a Notary is that legalization is an acknowledgment of the date of the agreement, so that a private deed that has been legalized provides certainty for the judge regarding the date, identity, and signature of the parties concerned and related to the agreement. In addition, as long as they still have the authority to carry out their duties as a Notary; 3) The legal consequences in evidence in court in the event that there is a private deed that is legalized by a notary are that it does not have perfect evidentiary power because it lies in the signatures of the parties which, if recognized, are perfect evidence like an authentic deed. In contrast to authentic deeds which have definite evidentiary power, for private deeds the evidentiary power lies in the hands of the judge to consider them (Article 1881 paragraph (2) of the Civil Code).